1997
DOI: 10.1002/(sici)1096-8628(19970905)71:4<436::aid-ajmg13>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

An apparently acentric marker chromosome originating from 9p with a functional centromere without detectable alpha and beta satellite sequences

Abstract: Recently, we studied a patient with minor abnormalities and an apparently acentric marker chromosome who carried a deleted chromosome 9 and a marker chromosome in addition to a normal chromosome 9. The marker was stable in mitosis but lacked a primary constriction. The origin of the marker was established by fluorescent in situ hybridization (FISH) using a chromosome 9 painting probe. Hybridization of unique sequence 9p probes localized the breakpoint proximal to 9p13. Additional FISH studies with all-human ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The centromere of the mammalian chromosome is generally considered critical for normal chromosome segregation. Acentric stably inherited chromosomes, however, have been reported [Voullaire et al, 1993; Ohashi et al, 1994; Blennow et al, 1994; Maraschio et al, 1996; Depinet et al, 1997; Vance et al, 1997, Tyler‐Smith et al, 1999]. Although the centromere is absent in some cases, a primary constriction is present.…”
Section: Introductionmentioning
confidence: 99%
“…The centromere of the mammalian chromosome is generally considered critical for normal chromosome segregation. Acentric stably inherited chromosomes, however, have been reported [Voullaire et al, 1993; Ohashi et al, 1994; Blennow et al, 1994; Maraschio et al, 1996; Depinet et al, 1997; Vance et al, 1997, Tyler‐Smith et al, 1999]. Although the centromere is absent in some cases, a primary constriction is present.…”
Section: Introductionmentioning
confidence: 99%
“…Marker chromosomes have now been identified that lack alphoid sequences yet have some degree of mitotic stability and possess a constriction similar to the primary constriction seen at the centromere [du Sart et al, 1997; Barry et al, 1999; for review, see Choo, 1997]. In addition, these marker chromosomes bind centromeric proteins in a manner consistent with a functional centromere [Ohashi et al, 1994; Vance et al, 1997; Depinet et al, 1997; du Sart et al, 1997; Tyler‐Smith et al, 1999]. These marker chromosomes provide evidence that the presence of α‐satellite sequences by itself is not a prerequisite for the formation of a functional centromere.…”
Section: Introductionmentioning
confidence: 99%
“…Nonsatellited and C‐band negative marker chromosomes should be tested for absence of alphoid sequences by use of an all centromere α‐satellite probe to assess for neocentromeres. Chromosome painting probes can provide confirmation of the origin of the marker, if the karyotype gives a preliminary indication [Abeliovich et al, 1996; Vance et al, 1997]. Spectral karyotyping [Huang et al, 1998] and subtelomeric probes (present study) can be used for other, unidentifiable acentric markers.…”
Section: Discussionmentioning
confidence: 95%